Effect of salinity levels on antifungal activity of essential oil from Thymus against Fusarium oxysporum - Boumaaza, Boualem; Benada, M’hamed; Boudalia, Sofiane; Benzohra, Ibrahim E.; Gacemi, Abdelhamid; Khaladi, Omar; Benkhelifa, Mohamed (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Thyme (Thymus sp.), a medicinal plant of the family Lamiaceae, is used in traditional medicine, contains a wide array of medicinally active components, in their great majority of a rather complex mixture of thymol, ρ-Cymene, γ-Terpinene, β-Caryophyllen, etc. This study aimed to evaluate the efﬁcacy of Thymus vulgaris extract against Fusarium oxysporum f. sp.radicis-lycopersici strain under saline conditions, assuming soil with high salt content of the arid regions. Essential oil was extracted by hydrodistillation technique using a Clevenger apparatus. The essential oil compounds were identified by GC-MS analysis. Antifungal activity of essential oil against Fusarium oxysporum f. sp. radicis-lycopersici was investigated by agar dilution method. The main constituents of thyme essential oil were thymol (76.96 %), ρ-cymene (9.89 %) and γ-Terpinene (1.92 %). Essential oil from Thymus resented high in vitro activity, in controlling conidial germination and mycelial growth. However, the oil was significantly not active against the spore production under a salinity medium. The results showed that mycelial growth was stimulated in concentrations with 0.6 -1.5 %. In contrast, it was significantly reduced at a higher concentration (2 %). The application of NaCl caused a significant increase in the conidia production at various concentrations tested. NaCl has a minor inhibitory effect on conidial germination only when the concentration was 2 %. The results of this study indicate that salinity decreases the efficacy of essential oil against the pathogen.